Enceintes romaines d'Aquitaine Bordeaux' Dax' Périgueux' Bazas - Garmy, Pierre; Maurin, Louis (Documents d'archéologie française, 1996)
Considered as the result of the barbarian invasions in 275 AD, four late roman town defences have been examinated here, Bordeaux, Dax, Périgueux and Bazas. The caracterstics of each one depend one depend on its past, on its role during the late roman period, on the various solutions adopted by the constructors and the date to which one can attribute the defances. However, in their general conception, the construction methods of the rampart, the details of organisation of defensive structures (positioning of towers, small number of gates, absence of ditches, abundance or rarety of reused building materials), these fortified towns do not represent individual cases but take their place within a system of defence created at different dates between the gallic empire and the end of roman domination in south-west Gaul